2017
DOI: 10.1080/10911359.2017.1313149
|View full text |Cite
|
Sign up to set email alerts
|

Parent–youth communication to reduce at-risk sexual behavior: A systematic literature review

Abstract: There are nearly 110 million cases of sexually transmitted infections (STI) in the United States. The Centers for Disease Control and Prevention estimates that annually there are more than 19.7 million new STI cases. Of those, more than half are accounted for by youth aged 15 to 24 years. Although some STIs are not considered to be life threatening, they can lead to severe health problems, risk of HIV infection or infertility if they are not properly treated. Some research has shown that parent-youth communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 36 publications
0
38
1
2
Order By: Relevance
“…Surprisingly, we identified that AA father-child bonding was negatively associated with HIV testing in Waves 1 and 3. These findings are not consistent with the literature that has documented how adolescents with parents who displayed warmth and caring are less likely to engage in sexual activity that would put them at risk for HIV and other sexually transmitted diseases (STDs) ( Coakley et al, 2017 ; Pengpid, & Peltzer, 2018 ; Rogers, 2017 ). This finding might suggest that adolescents have different bonding experiences with their fathers than their mothers.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Surprisingly, we identified that AA father-child bonding was negatively associated with HIV testing in Waves 1 and 3. These findings are not consistent with the literature that has documented how adolescents with parents who displayed warmth and caring are less likely to engage in sexual activity that would put them at risk for HIV and other sexually transmitted diseases (STDs) ( Coakley et al, 2017 ; Pengpid, & Peltzer, 2018 ; Rogers, 2017 ). This finding might suggest that adolescents have different bonding experiences with their fathers than their mothers.…”
Section: Discussioncontrasting
confidence: 95%
“…Thus, findings from this study, indicating that AA adolescents’ exposure to health care, in addition to father–child relationships, influences HIV testing, presents an apt intersection point that will benefit from further research on ways father–child relationships drive family-centered care within and beyond clinical settings. With the significant impact of HIV infection on the health and lives of AA adolescents, the results from our current study contribute toward addressing a much-needed knowledge gap in the ways to improve HIV testing and care ( Boyd, Lea, & Quinn, 2020 ; Nelson, Thach, et al 2015 ; Nelson, Wilton, et al 2015 ; Ogunbajo et al, 2020 ) and present father–child relationships as a promising area for future targeted interventions ( Coakley et al, 2017 )…”
Section: Conclusion and Future Directionmentioning
confidence: 95%
“…Whereas entitlement to pleasure was associated with both forms of sexual agency for White young women, it was only associated with sexual agency in the service of pleasure (not protection) for Black women. Discourses of sexual empowerment and agency aimed primarily at White young women tend to emphasize ideas of “owning one’s sexuality” and “being up for” sex (e.g., Bay-Cheng, 2015a; McRobbie, 2009), whereas controlling images of hypersexuality for Black girls (Collins, 2004) may yield particularly strong messages about their responsibility (and thus agency) to protect themselves (i.e., Coakley et al, 2017; Froyum, 2010). White young women also learn about the social and physical risks of acting on their sexual wants (Tolman & Chmielewski, 2018), but perhaps these lessons about dangers are nevertheless connected to ideals of entitlement to pleasure for these young women as they develop their sexual subjectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies support associations between parent–teen sexuality communication and teen sexual behavior. These studies primarily focus on mother–teen communication [4,10] and suggest that teen gender can shape these associations [4,11], although prior studies have not shown evidence for the moderating role of teen–parent relationships, such as closeness or relationship satisfaction. Research is needed to assess whether this model extends to adolescents’ sexuality communication with extended family.…”
Section: Introductionmentioning
confidence: 99%